2019
DOI: 10.1155/2019/8621951
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon from Prickly Pear Seed Cake: Optimization of Preparation Conditions Using Experimental Design and Its Application in Dye Removal

Abstract: In the present study, the experimental design method was used to optimize the preparation conditions of an activated carbon from prickly pear seed cake by phosphoric acid activation. The parameters studied include impregnation ratio, carbonization temperature, and carbonization time. The optimal conditions for the preparation of the activated carbon with high adsorption capacity for methylene blue were identified to be an impregnation ratio of 2.9, carbonization temperature of 541°C, and carbonization time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Activated carbon used in this study was prepared from prickly pear seed cake by phosphoric acid activation [33]. e authors reported that the obtained activated carbon is effective for removing cationic dyes such as methylene blue from aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated carbon used in this study was prepared from prickly pear seed cake by phosphoric acid activation [33]. e authors reported that the obtained activated carbon is effective for removing cationic dyes such as methylene blue from aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adsorption process was well described by the pseudo-second-order model and Freundlich isotherm. e adsorption capacity of the prepared activated carbon for methylene blue at temperature 20°C and pH ∼ 7 was found to be 260 mg/g [33]. To test the performance of the prepared activated carbon in the removal of anionic dyes from aqueous solution, methyl orange was chosen as a model adsorbate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also applied as a low-cost material for the treatment and removal of water containing COD, BOD, and TSS and stabilizing and maintaining the optimum pH for biological uses [154156]. Maguana et al prepared activated carbon from the pear seed cake and successfully applied it for the removal of methylene having an adsorption capacity of 260 mg/g [157]. Antonio et al prepared activated carbon from the kenaf plant and applied it successfully for the treatment of the wastewater of hospitals containing paracetamol as the main pollutant [158].…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Today, much effort is devoted to the exploitation of industrial waste and agricultural residues as raw materials for coal production. Among its products are walnut shells (Yang and Qiu, 2010), argan shells (Elmouwahidi, et al, 2012), snail shell (Gumus and Okpeku, 2014), olive nibs (Moubarik and Grimi, 2015), potato peel (Guechi et al 2016), sugar cane bagasse (Azmi et al, 2016), date press cake (Heidarinejad et al, 2018), betel nuts (Cundari et al, 2018) and prickly pear seeds (El Maguana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%